2017
DOI: 10.1016/j.is.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare support for underserved communities using a mobile social media platform

Abstract: Emerging digital technologies for healthcare information support have already contributed to reducing the digital divide among rural communities. Although mobile health (m-health) applications facilitate provision of support for treatment consultation in real-time, their substantial potential has not yet been operationalised for decision support to meet citizen demand in developing nations. Modern healthcare information access, especially in rural areas of developing countries, is critical to effective healthc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 46 publications
2
23
0
Order By: Relevance
“…That is, the positive external impacts of using an mHealth tool. These findings resonate with previous work demonstrating how perceived improvement in health outcomes could influence stakeholders' decision-making process towards positively appraising an mHealth tool (Aranda-Jan, Mohutsiwa-Dibe, & Loukanova, 2014;Miah, Hasan, Hasan, & Gammack, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…That is, the positive external impacts of using an mHealth tool. These findings resonate with previous work demonstrating how perceived improvement in health outcomes could influence stakeholders' decision-making process towards positively appraising an mHealth tool (Aranda-Jan, Mohutsiwa-Dibe, & Loukanova, 2014;Miah, Hasan, Hasan, & Gammack, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…While Emont (2011), suggested that PCHR would best suit people with low income, findings from this project suggest the opposite. Results from this project are inline more with other studies which suggested "digital divide" to be one of the barriers for adopting PCHR (Archer et al, 2011;Detmer et al, 2008;Kim et al, 2009;Miah et al, 2017;Patel et al, 2011;Roblin et al, 2009;Sciadas, 2002). Individuals with low income usually cannot afford computers or internet at their own homes.…”
Section: Usefulness/advantages and Disadvantagessupporting
confidence: 83%
“…Archer et al (2011;Patel et al, 2011). Kim et al (2009); (Miah, Hasan, Hasan, & Gammack, 2017); 3 Healthcare cultural and workflow issues (Archer et al, 2011;Detmer et al, 2008;Patel et al, 2011;Weitzman et al, 2009).…”
Section: Benefits Of Adopting Pchrsmentioning
confidence: 99%
“…The approach identified the patient's exercise, food, and emotional habits using mobile devices and sensors. Miah et al [31] designed and evaluated an innovative mobile decision support solution (MDSS) to support the health decisions of rural citizens and the dissemination of information. The solution was developed using a design science approach, allowing general practitioners, based on consultation and information support, to virtually assess patient conditions and provide a diagnosis or treatment.…”
Section: Related Workmentioning
confidence: 99%